Febrile infection-related epilepsy syndrome treated successfully with enteral lorazepam as a substitute for intravenous midazolam as weaning drug - Amarlok Kumar; Ravi Sharma; Preeti Kharwas; Anupam Chaturvedi; Vivek Jain (Wolters Kluwer Medknow Publications, 2021)
Febrile infection-related epilepsy syndrome (FIRES) is an acute-onset epilepsy syndrome usually refractory to conventional antiepileptics and immunomodulation. Here, we report an adolescent male child whose seizures were refractory to multiple anticonvulsants, high-dose phenobarbitone, and ketogenic diet. He subsequently responded to coma induction with midazolam, though with seizure recurrences following multiple attempts at weaning of midazolam over the next 2½ months. Due to continuing prolonged intensive care stay, we substituted intravenous midazolam for equivalent dose of enteral lorazepam with good seizure control.